2020
DOI: 10.3390/polym12122924
|View full text |Cite
|
Sign up to set email alerts
|

On the Strain Rate Sensitivity of Fused Filament Fabrication (FFF) Processed PLA, ABS, PETG, PA6, and PP Thermoplastic Polymers

Abstract: In this study, the strain rate sensitivity of five different thermoplastic polymers processed via Fused Filament Fabrication (FFF) Additive Manufacturing (AM) is reported. Namely, Polylactic Acid (PLA), Acrylonitrile-Butadiene-Styrene (ABS), Polyethylene Terephthalate Glycol (PETG), Polyamide 6 (PA6), and Polypropylene (PP) were thoroughly investigated under static tensile loading conditions at different strain rates. Strain rates have been selected representing the most common applications of polymeric materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 25 publications
6
63
0
Order By: Relevance
“…From these micro-cracks and while the material is being stressed at an external quasi static tensile field, it can be envisaged that some cracks could initiate and propagate in the longitudinal direction that the tensile test stress field is applied, resulting into a "plasticization"-like effect and yielding further to generally lower tensile modulus of elasticity values or, in other words, a knock-down effect on the material's modulus. Specifically, similar behavior has been also observed for ABS, PLA, HDPE and PP as reported in our previous recent study [37], corroborating the behavior that was also experimentally determined for PA12 tensile modulus of elasticity values in the study at hand.…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…From these micro-cracks and while the material is being stressed at an external quasi static tensile field, it can be envisaged that some cracks could initiate and propagate in the longitudinal direction that the tensile test stress field is applied, resulting into a "plasticization"-like effect and yielding further to generally lower tensile modulus of elasticity values or, in other words, a knock-down effect on the material's modulus. Specifically, similar behavior has been also observed for ABS, PLA, HDPE and PP as reported in our previous recent study [37], corroborating the behavior that was also experimentally determined for PA12 tensile modulus of elasticity values in the study at hand.…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…The results showed that PVC loaded with UFPNR had a rougher surface fracture than that of neat PVC. This implied that neat PVC had a brittle fracture mechanism [33]. With the addition of UFPNR content of up to 8 phr, a ductile fracture mechanism could be observed in the fracture surface of PVC, which was spanned by some drawn elongated fibrils.…”
Section: Application Of Ufpnr As Toughening Filler In Pvcmentioning
confidence: 95%
“…This potential of AM process in combination with bio-based materials, such as the PLA, creates a research need for the development of advanced composite materials. PLA has been thoroughly studied and it is continually under development with a large variety of fillers [2,8,21] and applications related to 3D printing for the development of composites with antimicrobial properties [22]. Polylactide is a famous polymer used in 3D printing, with an "easy-to-print" behavior.…”
Section: Introductionmentioning
confidence: 99%